A GAN-based federated learning architecture for data augmentation of medical images - Al Rakin, Abdullah; Iqbal Majumder, MD. Akib; Kabir, Mohammad Farhan; Arafin, Rudmila (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2022.